2004
DOI: 10.1016/j.jvs.2004.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species in inhibition of endothelial cell migration by oxidized low-density lipoprotein

Abstract: OxLDL inhibits endothelial cell migration, and may impair healing of arterial injuries. The mechanism of oxidized LDL inhibition is not known. Our in vitro studies show that the inhibitory properties are related to production of reactive oxygen species. Superoxide dismutase or inhibitors of reduced nicotinamide adenine dinucleotide phosphate oxidase can preserve endothelial migration in the presence of oxLDL. This might improve the healing of endothelial injuries at sites of arterial repair or angioplasty, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 48 publications
1
29
0
2
Order By: Relevance
“…LysoPC affects a number of cellular properties, including membrane fluidity, production of reactive oxygen species, intracellular calcium concentration, and other signaling pathways. [5][6][7] LysoPC can activate protein kinase C (PKC) in ECs, 8 but the specific isoforms activated have not been reported.…”
mentioning
confidence: 99%
“…LysoPC affects a number of cellular properties, including membrane fluidity, production of reactive oxygen species, intracellular calcium concentration, and other signaling pathways. [5][6][7] LysoPC can activate protein kinase C (PKC) in ECs, 8 but the specific isoforms activated have not been reported.…”
mentioning
confidence: 99%
“…30 However, excess levels of ROS are also detrimental as van Aalst et al showed that incubation of endothelial cells with oxidized lowdensity lipoprotein both increased ROS levels and decreased cell migration compared to cells cultured in a normal medium. 31 Prolonged exposure to ROS does not necessarily decrease CXCR4 expression as prior studies have shown that only very high levels of AGEs (500 lg/mL) decreased receptor expression. 12 Thus, ROS is a common intracellular messenger in the signaling pathways activated by CXCR4 and RAGE.…”
Section: Discussionmentioning
confidence: 91%
“…ROS dapat diinkubasi (CO 5%, 37°C, 24 jam) (22). Vitamin E (d-α-2 menghambat migrasi sel endotel, diantaranya melalui tokoferol; Sigma) 22 μM atau 50 μM dengan konsentrasi kerusakan sitoskeleton dan gangguan polimerisasi aktin akhir pelarut etanol <0,5% diberikan bersamaan dengan (15). Pemberian donor NO (16) dan superoxyde dismutase pemaparan glukosa.…”
Section: Diabetes Mellitus (Dm) Merupakan Kelainan Endokrinunclassified
“…Protein fungsional pada menghambat migrasi sel endotel. Selain itu, peroksinitrit membran sel membentuk berbagai macam reseptor dan juga dapat menghambat polimerisasi aktin yang penting struktur penting pada membran, diantaranya caveola yang untuk migrasi sel endotel (15).…”
Section: Dari Data T E Rs E B U T D I Ke T a H U I B A H W A V I T A unclassified